Analysis of the Impact of the Increase in Fuel Oil (BBM) on Household Economic Activities - Dinah Nadhifah; Ainun Mardiah; Nabila Suhaila Lubis; Muliana Fitri Lingga (Journal of Contemporary Gender and Child Studies, 2022)
Fuel oil (BBM) is one of the needs of the community in carrying out their activities. With the increase in fuel prices, the economic condition of the community becomes unstable. This paper aims to determine the condition of the people who are directly affected by the increase in fuel prices and the efforts made by the government to improve the welfare of its citizens in the current condition. The research was conducted with a qualitative approachwhich aims to understand and interpret the subject and provide an overview of the symptoms that appear. With data collection techniques using interviews are open-ended questions and documentation studies. Based on this research, it was found that there are clear impacts arising from the increase in fuel oil (BBM), starting from the lack ofcommunity income, public transport fares, purchasing power, and so on. And the government is trying to overcome this problem by providing assistance to the community in the form of direct cash assistance (BLT), wage subsidies, transportation assistance, and additional social protection for online motorcycle taxis, public transportation, and fishermen.